Composite materials formed using polyols polymerized with lewis acids and methods of making same

By using Lewis acid-catalyzed polyether polyols and perfluoroalkyl-substituted arylborane catalysts, the demolding time and compatibility issues of polyurethane formulations have been resolved, achieving rapid curing and improved mechanical properties, making them suitable for the processing and application of composite materials.

CN121358593APending Publication Date: 2026-01-16DOW GLOBAL TECHNOLOGIES LLC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380099570.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-06
Publication Date
2026-01-16

AI Technical Summary

Technical Problem

Existing polyurethane formulations have issues with demolding time and compatibility. The use of high concentrations of ethylene oxide polyols leads to increased hygroscopicity and reduced compatibility with non-polar formulation components, affecting production efficiency and product quality.

Method used

A mixture of isocyanate and isocyanate reactive components is formed by increasing the concentration of primary hydroxyl groups in a polyether polyol catalyzed by Lewis acid via a perfluoroalkyl-substituted arylborane catalyst, thereby improving reactivity and compatibility, and is then processed in the presence of reinforcing materials.

Benefits of technology

It achieves rapid demolding and improved mechanical strength, while maintaining good compatibility, reducing phase separation and discoloration problems, and improving production efficiency and product quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

A method can include preparing a reaction mixture by combining: an isocyanate component; and an isocyanate-reactive component comprising at least one Lewis acid catalyzed polyether polyol having 90 weight percent (wt.%) or more of polypropylene oxide, a primary hydroxyl group concentration of at least 30 weight percent, a functionality of at least 2, an OH number in the range of 100 mg KOH / g to 800 mg KOH / g, and an average acetal content of at least 0.05 weight percent, the isocyanate-reactive component comprising at least one Lewis acid catalyzed polyether polyol having 90 weight percent (wt.%) or more of polypropylene oxide, a primary hydroxyl group concentration of at least 30 weight percent, a functionality of at least 2, an OH number in the range of 100 mg KOH / g to 800 mg KOH / g; and combining the reaction mixture with one or more reinforcing materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The implementation scheme relates to polyurethane and polyurethane / (methacrylate) blend compositions for producing polyurethane composites and reinforcing materials with improved mechanical properties. Background Technology

[0002] Polyurethane (PU) formulations can be manufactured into reinforced composites using various processes, including pultrusion, infusion, and filament winding. Pultrusion is a continuous manufacturing process used to produce fiber-reinforced polymer composite profiles with a constant cross-sectional area, typically used in structural applications. Infusion is a process that involves applying a vacuum to bring PU resin into contact with and impregnate the fibers, and it is used to manufacture articles such as wind turbine blades. Conversely, filament winding is typically used to manufacture articles such as pipes or closed-end structures (pressure vessels or tanks) involving the winding of pre-impregnated resin filaments onto a rotating mandrel.

[0003] As with most manufacturing techniques, reducing demolding time while maintaining or improving product quality leads to increased productivity. To reduce demolding time, higher catalyst loadings or polyols containing higher concentrations of reactive primary hydroxyl groups (e.g., ethylene oxide (EO) derivatives) can be used. However, the use of polyurethane catalysts can be prohibitively expensive and may increase volatility and shorten the curing time of the formulation during processing. EO can be used as an alkoxylating agent to obtain polyols containing high concentrations of primary hydroxyl groups, resulting in higher hygroscopicity and potential water accumulation in the formulation upon exposure to the atmosphere. The increased polarity of EO-containing polyols can also lead to compatibility issues with non-polar formulation components, as well as problems with haze and turbidity. Summary of the Invention

[0004] In one aspect, embodiments of the present disclosure include a method for forming a composite material, the method comprising: preparing a reaction mixture by combining the following substances: an isocyanate component; and an isocyanate reactive component comprising at least one Lewis acid-catalyzed polyether polyol having 90 wt% or more of polypropylene oxide, at least 30 wt% of primary hydroxyl concentration, at least 2 functionality, an OH value in the range of 100 mg KOH / g to 800 mg KOH / g, and at least 0.05 wt% of average acetal content; and combining the reaction mixture with one or more reinforcing materials. Detailed Implementation

[0005] The embodiments relate to two-component polyurethane and polyurethane / (meth)acrylate blends for the manufacture of composite materials, the compositions comprising a Lewis acid-catalyzed polyether polyol produced by polymerization in the presence of a perfluoroalkyl-substituted arylborane catalyst. The polymer-forming composition comprises an isocyanate component and an isocyanate reactive component, the isocyanate reactive component comprising at least the Lewis acid-catalyzed polyether polyol. The Lewis acid-catalyzed polyether polyol disclosed herein may have 90 wt% or more of polypropylene oxide, at least 30 wt% of primary hydroxyl concentration, at least 2 functionality, an OH value in the range of 100 mg KOH / g to 800 mg KOH / g, and at least 0.05 wt% of average acetal content. The method also includes forming the composite material by combining the components using a suitable process such as infusion, pultrusion, or filament winding in the presence of a reinforcing material.

[0006] Using Lewis acid polymerization catalysts (such as perfluoroalkyl-substituted arylborane catalysts) to produce polyether polyols can improve the reactivity of the polyol with the isocyanate component by increasing the percentage of primary hydroxyl groups, particularly for polyether polyols based on (or containing) polypropylene oxide. Increased concentrations of primary hydroxyl groups are associated with faster curing times and improved appearance of the final product. Comparative formulations containing a certain concentration of polyethylene oxide to increase the percentage of primary OH-terminal functional groups result in some reduction in demolding time during manufacturing. However, the presence of polyethylene oxide also leads to reduced compatibility with nonpolar polymer phases and layers (such as PVC surface layers), resulting in open-cell structures that are easily discolored by oxidizing gases, and scorching associated with high reactivity. On the other hand, polypropylene oxide-based polyether polyols exhibit good compatibility with nonpolar phases, but the preparation of polyether polyols from monomers with more than 2 carbon atoms (i.e., propylene oxide, butane oxide) via standard KOH alkoxylation catalysis produces products with >95% secondary OH groups.

[0007] The PU compositions and composites disclosed herein comprise polyether polyols produced by Lewis acid-catalyzed polymerization, which increases the percentage of primary hydroxyl groups and associated performance properties (e.g., reactivity, demolding time, etc.). The PU compositions and composites disclosed herein exhibit rapid demolding and cycle times, while unexpectedly demonstrating enhanced mechanical strength relative to KOH-catalyzed PO-based contrast polyols, and less phase separation during processing compared to EO-based contrast polyols. In some cases, PU formulations containing Lewis acid-catalyzed polyether polyols can enable the formation of composites with good mechanical properties and good adhesion to PVC surfaces. According to ASTM D7487-18, such as those produced by FOAMAT... ™The PU compositions disclosed herein have been determined by the Foam Qualification System (Foamat Messtechnik GmbH, Karlsruhe, Germany) to be capable of rapid curing over long working times.

[0008] The PU compositions disclosed herein typically comprise a product obtained by combining a two-component curable composition: an isocyanate component (“A side”) and an isocyanate reactive component (“B side”). During application, the isocyanate and the isocyanate reactive component are mixed to initiate a curing reaction and form a PU composition or composite. During the formation of the PU composite, the isocyanate component and the isocyanate reactive component may be combined in the presence of a reinforcing material (e.g., carbon fiber, glass fiber). In some cases, the reinforcing material may be combined with at least one of the isocyanate or the isocyanate reactive component prior to PU formation, or may be present as a third component combined after the mixture of the isocyanate and the isocyanate reactive component. The compositions disclosed herein may be substantially anhydrous (i.e., at a maximum content of 0.1% or less in the formulation) and produce negligible amounts of foam when the reactant components are combined.

[0009] The isocyanate component may contain one or more isocyanate compounds, such as polymeric isocyanates, aromatic isocyanates, or carbodiimide-modified isocyanates. The isocyanate compounds may be monomers, oligomers, prepolymers, etc. The isocyanate component may include, for example, one or more isocyanate and / or polyisocyanate compounds. The isocyanate component may contain isocyanate compounds having a nominal functionality of 1.5 or greater, or ≥2.0 or greater.

[0010] The isocyanate component may include isocyanate compounds having a number average molecular weight of 150 g / mol to 750 g / mol. In some cases, the number average molecular weight of the isocyanate compound may be as low as 150 g / mol, 200 g / mol, 250 g / mol, or 300 g / mol to as high as 350 g / mol, 400 g / mol, 450 g / mol, 500 g / mol, or 750 g / mol. The number average molecular weight values ​​reported herein were determined by end-group analysis, gel permeation chromatography, and other methods known in the art. The isocyanate compound may be monomeric and / or polymeric, as known in the art.

[0011] Isocyanate components may include one or more of aliphatic polyisocyanates, alicyclic polyisocyanates, aryliphatic polyisocyanates, and aromatic polyisocyanates. Examples of isocyanates include, but are not limited to, methylene diphenyl diisocyanate (MDI, including its isomers); polymeric MDI; triisocyanatononane (TIN); naphthyl diisocyanate (NDI); 4,4'-diisocyanate dicyclohexyl-methane; 3-isocyanomethyl-3,3,5-trimethylcyclohexyl isocyanate (isophorone diisocyanate, IPDI); tetramethylene diisocyanate; hexamethylene diisocyanate (HDI); 2-methyl-pentamethylene diisocyanate; 2, 2,4-Trimethylhexamethylene diisocyanate (THDI); dodecamethyl diisocyanate; 1,4-diisocyanocyclohexane; 4,4'-diisocyano-3,3'-dimethyl-dicyclohexylmethane; 4,4'-diisocyano-2,2-dicyclohexylpropane; 3-isocyanomethyl-1-methyl-1-isocyanocyclohexane (MCI); 1,3-diisooctylcyano-4-methylcyclohexane; 1,3-diisocyano-2-methylcyclohexane; and combinations thereof. In addition to the isocyanates mentioned above, partially modified polyisocyanates may be used, including urea diketones, isocyanurates, carbodiimides, urea ketone imides, urea carbamates, or biuret structures, and combinations thereof. Examples of commercial isocyanates include, but are not limited to, those marketed under the trade name VORANATE. ™ VORATRON ™ PAPI ™ VORAFORCE ™ and ISONATE ™ Polyisocyanate purchased from Dow Chemical Company.

[0012] The isocyanate component may include isocyanate prepolymers obtained by reacting an isocyanate reactive compound with a molar excess of a polyisocyanate compound or a polymeric isocyanate compound under conditions that do not lead to gelation or curing, and these isocyanate prepolymers may have a high average isocyanate equivalent weight of >140 g / eq. The formation of isocyanate prepolymers is known in the art and may include reacting (1) at least one isocyanate compound and (2) at least one polyol compound. The isocyanate prepolymer can be described by NCO% which corresponds to the weight percentage of NCO groups remaining after the reaction between the isocyanate present in the prepolymer and the isocyanate reactive compound is completed. The isocyanate components disclosed herein may comprise one or more isocyanate compounds having an NCO content of 20% or more, such as in the range of 20% to 50% or 20% to 48% by weight.

[0013] The isocyanate component comprises at least one material containing isocyanate groups (such as polyisocyanates and / or isocyanate-terminated prepolymers). For example, the isocyanate component comprises at least one aromatic polyisocyanate, such as methylene diphenyl diisocyanate (MDI) and / or toluene diisocyanate (TDI). To form a polyurethane polymer, the isocyanate and isocyanate reactive components can be mixed and applied to a substrate before use, and / or applied separately to the substrate and allowed to mix on the substrate. Based on the total weight of the isocyanate component, the isocyanate component may contain at least 50% by weight (at least 60% by weight, at least 70% by weight, at least 80% by weight, at least 90% by weight, at least 95% by weight, at least 98% by weight, etc.) of one or more polyisocyanates.

[0014] The PU compositions disclosed herein may contain isocyanate components in the range of 15% to 80%, 20% to 80%, or 20% to 70% by weight.

[0015] The PU composition may contain an isocyanate reactive component comprising at least one polyether polyol prepared using a Lewis acid catalyst, and optionally one or more hydroxyl-functionalized (meth)acrylates. As used herein, “(meth)” when used with various acrylate substances indicates that the scope of this specification covers both the acrylate and methacrylate variants of the compounds mentioned.

[0016] Lewis acid-catalyzed polyether polyols can be prepared by polyaddition (alkoxylation) of alkyl epoxides onto an initiator (i.e., a polyhydroxy functional initiator compound) in the presence of a catalyst known in the art, which can shape the ratio of primary to secondary hydroxyl groups in the resulting polymer or oligomer. For example, alkoxylation using a Lewis acid catalyst results in an increase in the amount of primary hydroxyl groups, while the use of a basic catalyst such as KOH produces secondary hydroxyl groups as the major product. Representative methods for producing polyether polyols using Lewis acid catalysts are discussed, for example, in WO2019055725 and WO2019055727.

[0017] The initiator comprises one or more compounds having a low molecular weight and a numerical hydroxyl functionality of at least 2. The initiator is any organic compound that will be alkoxylated in the polymerization reaction. The initiator may contain up to 10 hydroxyl groups. For example, the initiator may be a diol or a triol. Mixtures of initiators may be used. The hydroxyl equivalent of the initiator will be less than the hydroxyl equivalent of the polyether product, for example, it may have a hydroxyl equivalent of less than 500 g / mol, less than 300 g / mol, greater than 20 g / mol, 20 g / mol to 300 g / mol, 20 g / mol to 200 g / mol, 30 g / mol to 150 g / mol, etc. Exemplary initiator compounds include ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, tripropylene glycol, 1,4-butanediol, 1,6-hexanediol, 1,8-octanediol, cyclohexanediol, bisphenol A, glycerol, trimethylolpropane, trimethylolethane, pentaerythritol, sugars and sugar alcohols (such as sorbitol and sucrose) and / or alkoxylates, any of which have a weight-average molecular weight lower than that of the polymerization product.

[0018] Lewis acid-catalyzed polyether polyols may have a functionality of at least 2 or higher (e.g., in the range of 2 to 6 or 2 to 4). Lewis acid-catalyzed polyether polyols may have an average primary hydroxyl content of at least 25% or more, or 30% or more (e.g., 25% to 85%, or 30% to 80%). The Lewis acid-catalyzed polyols disclosed herein may have low VOC content (e.g., propionaldehyde and acetal) and selectivity up to 85% for PO-derived primary hydroxyl-terminated polyol chains. Lewis acid-catalyzed polyether polyols may have an average acetal content of at least 0.05% by weight, or at least 0.1% by weight.

[0019] Lewis acid catalysts can be arylborane catalysts having at least one fluorine / chlorine or fluoroalkyl-substituted phenyl group, which can allow for improved reaction yields. The polymerization catalyst can be fed into the reactor in an amount greater than 0 and less than or equal to 0.005 (e.g., greater than 0.0001, less than or equal to 0.003, less than or equal to 0.001, etc.) molar equivalents per molar initiator. Lewis acid catalysts can be active in a lower temperature range (e.g., 60°C–110°C).

[0020] Lewis acid polymerization catalysts have the general formula M(R) 1 )1(R 2 )1(R 3 )1(R 4 ) 0或1 Where M is boron, aluminum, indium, bismuth, or erbium, and R 1 Containing a first fluorine / chlorine or fluoroalkyl-substituted phenyl group (e.g., composed of such a group), R 2Containing a second fluorine / chlorine or fluoroalkyl-substituted phenyl group (e.g., composed of such a group), R 3 Contains a phenyl group or a first functional group or a functional polymer group substituted with a third fluoro / chloro or fluoroalkyl group (e.g., composed of such a group), and optionally R 4 It is a second functional group or a functional polymer group (e.g., composed of such a group). As used herein, a fluorine / chlorine or fluoroalkyl-substituted phenyl group refers to a fluorine / chlorine-substituted phenyl group or a fluoroalkyl-substituted phenyl group as described below. A fluoroalkyl-substituted phenyl group is a phenyl group containing at least one hydrogen atom replaced by a fluoroalkyl group. A fluorine-substituted phenyl group is a phenyl group containing at least one hydrogen atom replaced by a fluorine atom. A chlorine-substituted phenyl group is a phenyl group containing at least one hydrogen atom replaced by a chlorine atom. A fluorine / chlorine-substituted phenyl group is a phenyl group containing at least one hydrogen atom replaced by a fluorine or chlorine atom, and the phenyl group may contain a combination of fluorine and chlorine substituents. R 1 R 2 and R 3 Each group may independently contain fluorine / chlorine or fluoroalkyl-substituted phenyl groups, or may independently consist substantially of fluorine / chlorine or fluoroalkyl-substituted phenyl groups. M in the general formula may exist as a metal salt ion or as an integral bonding portion of the formula.

[0021] Regarding R 3 and optional R 4 The functional group or functional polymer group can be a Lewis base that forms a complex with a Lewis acid catalyst (e.g., a boron-based Lewis acid catalyst) and / or a molecule or portion containing at least one electron pair that can form a coordinate bond with a Lewis acid. A Lewis base can be a polymeric Lewis base. The functional group or functional polymer group refers to a molecule containing at least one of the following: water, alcohol, alkoxy group (examples include straight-chain or branched ethers and cyclic ethers), ketone, ester, organosiloxane, amine, phosphine, oxime, and their substituted analogs. Each of alcohols, straight-chain or branched ethers, cyclic ethers, ketones, esters, alkoxy groups, organosiloxanes, and oximes may contain 2-20 carbon atoms, 2-12 carbon atoms, 2-8 carbon atoms, and / or 3-6 carbon atoms. For example, the functional group or functional polymer group may have the formula (OYH). n In this formula, O is oxygen, H is hydrogen, Y is H or a hydrocarbon group, and n is an integer (e.g., an integer from 1 to 100). However, other known functional polymer groups that can be combined with Lewis acid catalysts, such as boron-based Lewis acid catalysts, can be used. Exemplary cyclic ethers include tetrahydrofuran and tetrahydropyran.

[0022] In some cases, the Lewis acid polymerization catalyst can be the Lewis acid polymerization catalyst shown in Structure I.

[0023]

[0024] Lewis acid-catalyzed polyether polyols may have OH values ​​in the range of 100 mg KOH / g to 900 mg KOH / g, 100 mg KOH / g to 800 mg KOH / g, or 100 mg KOH / g to 750 mg KOH / g. Lewis acid-catalyzed polyether polyols may have number-average molecular weights of 400 Da or greater, 450 Da or greater, or 500 Da or greater (such as in the range of 400 Da to 2000 Da, or 400 Da to 1500 Da).

[0025] Lewis acid-catalyzed polyether polyols may have a polypropylene oxide content of 80% by weight or higher, or 90% by weight or higher. In some cases, Lewis acid-catalyzed polyether polyols may include polypropylene oxide homopolymers (including polypropylene oxide homopolymers polymerized in the presence of polyhydroxy initiator compounds).

[0026] Lewis acid-catalyzed polyether polyols may be present in the isocyanate reactive component at a weight percentage (wt%) of at least 10 wt% or at least 20 wt% (such as in the range of 10 wt% to 95 wt%, 15 wt% to 95 wt%, or 15 wt% to 80 wt%).

[0027] The isocyanate reactive component may include one or more hydroxyl-functional (meth)acrylate monomers, which react with the isocyanate component and / or polymerize in the presence of a free radical initiator to produce a PU acrylate blend composition. The hydroxyl-functional (meth)acrylate monomers may have the following general formula:

[0028]

[0029] Wherein R1 is selected from hydrogen, methyl, or ethyl; R2 is selected from alkylene groups having 2 to 6 carbon atoms, 2,2-bis(4-phenylene)propane, 1,4-bis(methylene)benzene, 1,3-bis(methylene)benzene, 1,2-bis(methylene)benzene; and n is an integer selected from 1 to 6. Hydroxyl-functional (meth)acrylate monomers may include hydroxy C1-10 (meth)acrylate alkyl ester monomers, such as hydroxyethyl acrylate, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate monomers, etc.

[0030] The amount of hydroxyl-functional (meth)acrylate added can be in the range of 15% to 40% by weight, 20% to 38% by weight, 25% to 35% by weight, or 27% to 32% by weight, based on the weight percentage (wt%) of the polyurethane acrylate blend.

[0031] The isocyanate reactive component may include one or more anthraquinone curing indicators, which provide a visual indication of the progress of the PU acrylate blend during curing. In some cases, curing may be indicated by a change from light green to brownish-red, indicating that the composition is substantially cured. Suitable anthraquinone curing indicators include anthraquinone dyes such as 1-(methylamino)-4-p-toluidine anthraquinone (CAS: 128-85-8), 1,4-bis(ethylamino)-9,10-anthraquinone, 1,4-bis(4'-methylphenylamino)anthraquinone, 1,4-bis(o-sulfo-p-toluidine)anthraquinone, etc.

[0032] The amount of anthraquinone curing indicator added can be in the range of 0.001% to 0.15% by weight, 0.001% to 0.10% by weight, or 0.01% to 0.05% by weight, based on the weight percentage (wt%) of the polyurethane acrylate mixture.

[0033] The methods disclosed herein may include forming composite articles and materials by any suitable method. In some cases, composite components are prepared by combining isocyanates and isocyanate reactive compounds to form a reactive mixture, and then combining it with a reinforcing material. Suitable reinforcing materials include any and more of glass fibers, electronic-grade glass fibers (e-glass fiber), carbon nanotubes, carbon fibers, polyester fibers, natural fibers, glass fibers, aramid fibers, nylon fibers, mineral fibers, basalt fibers, boron fibers, silicon carbide fibers, asbestos fibers, whiskers, hard particles, metal fibers, etc.

[0034] Methods for forming composite materials may include vacuum-assisted resin transfer molding (VARTM, also known as infusion molding), pultrusion, filament winding or braiding, reinforced reactive injection molding (RRIM), structural reactive injection molding (SRIM), resin transfer molding (RTM), in-situ curing pipe applications, reactive extrusion, and other reactive processing techniques. Reactive processing techniques may include producing composite materials in a single step, such as polymer material formation and reinforcement occurring in the same step or cycle.

[0035] In some cases, the pultrusion process may include drawing a pre-selected reinforcing material (such as glass fiber roving, padding, or fabric) through a resin bath in which the reinforcing material is thoroughly impregnated with a toughened PU or PU / (meth)acrylate blend. The soaked fibers can then be formed into the desired geometry and drawn into a heated steel mold. Once inside the mold, curing of the toughening composition is initiated by controlling the temperature within the mold. The laminate cures in the shape of the mold as it is continuously drawn through a pultrusion machine. Compositions and methods have been discussed with respect to examples of polyurethane composites produced by infusion or pultrusion; however, it is contemplated that polyurethane composites may be produced by any suitable method without departing from the scope of this disclosure.

[0036] Cured articles made from curable resin compositions can be used to produce composite materials, articles, coatings, adhesives, inks, encapsulations, or castings. Composite materials can be used in applications such as wind turbines (e.g., spar caps, wind turbine blades), ship hulls, truck bed covers, automotive trim and exterior panels, pipes, tanks, window liners, seawalls, pressure vessels, composite ladders, etc.

[0037] Although the formulation components and properties have been disclosed individually, it is contemplated that any of the above concentration ranges and nested subranges therein can be used to include, exclude, or combine component elements (e.g., compounds in isocyanate or isocyanate reactive components) in any manner or sub-combination. Furthermore, the formulation properties can be similarly achieved through various combinations of the components within the ranges.

[0038] Unless otherwise specified, all parts and percentages are by weight. Unless otherwise specified, all molecular weight values ​​are based on number-average molecular weight.

[0039] Example

[0040] The following examples are provided to illustrate embodiments of the invention, but are not intended to limit the scope of the invention. Table 1 provides the materials used in the following examples.

[0041]

[0042] Example 1: Polyurethane Composite Formulation

[0043] In this embodiment, polyurethane compositions were prepared to analyze the properties of the present invention samples and comparative samples containing polypropylene oxide-based polyols. The present invention samples (I1-I3) were formulated with Lewis acid-catalyzed PO-based polyols at three different loading levels (from 20 parts to 55 parts), and the results were compared with comparative formulations (C1-C3) formulated with polyol 2 (having the same OH value and functionality, but prepared via KOH catalysis). The formulations are shown in Table 2.

[0044]

[0045] Unless otherwise specified in the test method, samples are typically prepared by mixing the appropriate components of the isocyanate reactive component using a DAC 600.1 FVZ-K speed mixer until uniformly dispersed. The isocyanate components are then combined and mixed at the specified ratio. The mixture is poured into a suitable mold, and the mold is transferred to an oven at 100°C and maintained for 90 minutes. The plate is then demolded, and the test sample shape is water-jet cut accordingly.

[0046] The testing methods are as follows. The property measurement results for each sample are shown in Table 3.

[0047] Viscosity: Viscosity rise was measured using a Brookfield DV-II+ Pro viscometer. For each sample, the isocyanate and isocyanate reactive component were mixed at 2350 RPM for 15 seconds according to Table 5 to ensure the same sample temperature each time. 10 g to 10.5 g of the mixture (depending on the mixing ratio) was poured into a disposable chamber (HT-2DB-100) and then dropped into a Thermosel (Brookfield Engineering). The Thermosel was maintained at an isothermal temperature of 26°C. Viscosity rise over time was then measured using a disposable spindle (SC4-27).

[0048] Glass transition temperature and storage modulus using DMA: Dynamic mechanical analysis (DMA) was performed using an Advanced Rheological Extension System (ARES-G2) from TA Instruments equipped with a liquid nitrogen environment control, employing a torsion rectangular fixture. A 3 mm thick rectangular sample (45 mm long and 12.8 mm wide) of foam prepared in a metal mold was stamped. The temperature was increased from -70 °C to 200 °C at a heating rate of 3 °C / min. The test frequency was 1 Hz, with an axial force of 0.098 N, a strain of 0.05%, and a data collection interval of 30 sec / point. The main outputs identified from the characterization were the storage modulus (G') and Tan δ in shear modulus.

[0049] Tensile modulus, elongation at break, and ultimate tensile strength: Elongation at break (%), ultimate tensile strength (MPa), and tensile modulus (MPa) were obtained using ASTM D1708 on an MTS machine. Cured samples of 3 mm thickness were tested after molding (and aged for at least 2 days under ASTM conditions). The micro-stretched samples were then stamped into a dog-bone shape.

[0050] Cantilever Beam Impact Test (IZOD): The sample was molded to a length of 45 mm, a width of 12.7 mm, and a thickness of 3 mm. A 2.54 mm grooving was made in the center of the sample. The grooving was performed using a CEAST Notchvis automatic grooving machine (POR-TL-090). Impact resistance was measured at 23°C and 50% relative humidity using a 92T model with an 892 impact display system, according to ASTM D256 (Method for Determining the Impact Resistance of Plastics by Cantilever Beam Pendulum).

[0051]

[0052] In Table 3, I1-I3 are characterized by a better reactivity profile (faster reactivity), the effect of which is proportional to the amount of Lewis acid-catalyzed polyol in the formulation. However, the curing time remains acceptable, as the mixed viscosity is <1000 cPs after 10 minutes, and the samples of this invention exhibit unexpectedly improved polymer properties, including higher glass transition temperature, modulus, elongation, and tensile strength.

[0053] Example 2: Compatibility / miscibility of polyols in formulations

[0054] In this embodiment, the compatibility / miscibility of various isocyanate reactive component formulations was tested by combining the formulation components shown in Tables 4 and 5 according to the method described in Example 1. After combination, the formulations were sealed in glass vials and allowed to stand on a horizontal surface at room temperature for one week. Phase separation and discoloration of the samples were visually inspected.

[0055] In the samples, the formulations incorporated various concentrations of polyol 2 (C4-C6), polyol 4 (C7-C9), and Lewis acid-catalyzed polyols (I4-I6). In all formulations, the ratio of polyol 1 to polyol 3 remained approximately constant.

[0056]

[0057]

[0058] For isocyanate reactive components prepared using polyol 2 (a glycerol-initiated, all-PO polyether polyol with >95% secondary OH end groups), none of the samples (at 20 wt%, 40 wt%, and 55 wt%) showed phase separation or discoloration / color change, indicating their suitability for pultrusion applications.

[0059] Similarly, the isocyanate reactive components prepared using the major polyol components of the polyol catalyzed by Lewis acids are stable, with no visible phase separation or discoloration / color change at 20 wt% loading, 40 wt% loading, and 55 wt% loading.

[0060] However, samples C7-C9 formulated with polyol 4 (glycerol-initiated polyol, all-EO) at loadings of 20 wt%, 40 wt%, and 55 wt% showed phase separation a few days after preparation. The degree of phase separation was estimated to be about 15 vol% or higher, depending on the polyol loading. The presence of phase separation represents a problem for the formulation resin intended for composite applications. The samples also showed progressive discoloration and a slight yellowing over time, indicating undesirable side reactions. Phase separation is thought to be due to the poor compatibility of all-EO polyols with other formulation components. Therefore, while the use of all-EO polyols is expected to provide accelerated reactive distribution compared to PO-based polyols, phase separation limits their usefulness in composite forming applications.

[0061] Example 3: Design of a dense complex formulation for infusion applications

[0062] In this embodiment, a polyurethane / acrylate blend was prepared as a dense composite material, and various performance parameters were measured. The polymer sample was prepared essentially as described in Example 1. The formulation and results are shown in Table 6.

[0063] The testing method is as follows.

[0064] Tensile and impact properties: 1. After the chemical temperature reaches 25°C, add 100g of isocyanate and 100g of the prepared polyol to a 1000ml high-speed mixer cup. Mix the mixture through the high-speed mixer at 1500rpm for 1 minute. 2. Remove air bubbles from the PU resin using vacuum, then pour the resin into a steel mold. The mold cavity dimensions are 20cm × 20cm × 0.4cm. 3 The resin will gel and cure in the mold after the following curing cycles: 2 hours at 50°C + 6 hours at 70°C. 4. Demold to obtain the cast plate for testing. 5. Process test samples from the cured cast plate according to ISO 527 and ISO 179. 6. Conduct tests and record the relevant mechanical properties.

[0065] Tensile properties (strength, modulus, elongation at break) test conditions: ISO 527-2, test speed: 2 mm / min.

[0066] Impact property test conditions: ISO 179, impact velocity: 2.9 m / s, impact energy: 4 J.

[0067] While the foregoing relates to exemplary embodiments, other and additional embodiments may be devised without departing from the basic scope of the invention, the scope of which is defined by the appended claims.

[0068]

[0069] In the results, I7, a polyol containing Lewis acid catalysis, exhibited a relatively longer settling time than C10, followed by faster curing. Table 6 also shows that Lewis acid-catalyzed polyols unexpectedly led to the formation of polymers with improved mechanical properties in both strength and elongation compared to polyol 2. Formulations for composite manufacturing technologies such as infusion or pultrusion are expected to have longer settling times and preferably slow viscosity build-up to achieve fiber wetting and rheology during processing. Furthermore, rapid curing of the formulation after the gelation reaction begins is important, resulting in excellent final mechanical properties, good wetting properties, and no bubble formation.

[0070] While the foregoing relates to exemplary embodiments, other and additional embodiments may be devised without departing from the basic scope of the invention, the scope of which is defined by the appended claims.

Claims

1. A method of forming a composite material, the method comprising: preparing a reaction mixture by combining: an isocyanate component; and an isocyanate-reactive component, the isocyanate-reactive component comprising at least one Lewis acid-catalyzed polyether polyol having 90 weight percent (wt%) or more polypropylene oxide, a primary hydroxyl concentration of at least 30 wt%, a functionality of at least 2, an OH number in the range of 100 mg KOH / g to 800 mg KOH / g, and an average acetal content of at least 0.05 wt%; and combining the reaction mixture with one or more reinforcing materials.

2. The method of claim 1, wherein the isocyanate-reactive component comprises at least 10 wt% of the polyether polyol.

3. The method of claim 1, wherein the polyether polyol is a polypropylene oxide polyol.

4. The method of claim 1, wherein the composite material has a density higher than 0.850 g / mL.

5. The method of claim 1, wherein the polyether polyol has a weight average molecular weight of 200 Da to 1,000 Da and a functionality of 2 to 4.

6. The method of claim 1, wherein the Lewis acid catalyst used to produce the polyether polyol has the general formula M(R 1 )1(R 2 )1(R 3 )1(R 4 ) 0或1 where M is boron, aluminum, indium, bismuth, or erbium, R 1 , R 2 , R 3 , and R 4 are each independent, R 1 comprises a first fluoro / chloro or fluoroalkyl substituted phenyl group, R 2 comprises a second fluoro / chloro or fluoroalkyl substituted phenyl group, R 3 comprises a third fluoro / chloro or fluoroalkyl substituted phenyl group or a first functional group or functional polymeric group, and optional R 4 is a second functional group or functional polymeric group.

7. The method of claim 1, wherein the isocyanate-reactive component further comprises a hydroxyl (meth)acrylate monomer, a prepolymer, or a polymer.

8. The method of claim 1, wherein the isocyanate component is present in a weight percent (wt%) in the range of 35 wt% to 65 wt% of the reaction mixture.

9. The method of claim 1, wherein the method for forming the composite material comprises pultrusion, infusion, or filament winding.

10. A composite material prepared by the method of claim 1.

Citation Information

Patent Citations

  • Process of manufacturing polyols

    WO2019055725A1

  • Process of manufacturing polyols

    WO2019055727A1